Evaluation of Diaphragmatic Ultrasound in Respiratory Functional Assessment in Patients with ALS - Miguel Iglesias; Juan Alejandro Cascón; Andrés Maimó; Antonio Albaladejo; Felipe Andreo; Ana Sánchez Fernández; María Maciá Palazón; Isabel Martínez González-Posada; Ruth García García; Rosa Cordovilla (Diagnostics)
Background: Diaphragmatic ultrasound emerges as a valuable non-invasive method for assessing diaphragm functionality in patients with amyotrophic lateral sclerosis (ALS). This study aimed to evaluate diaphragmatic ultrasound parameters in ALS, compare them with respiratory function tests, and determine whether they are associated with the need for non-invasive ventilation (NIV). Methods: This was a prospective, descriptive, and multicenter study across five centers, enrolling patients with recent diagnoses of ALS. At three-monthly visits, participants underwent both diaphragmatic ultrasound and pulmonary function testing. The following variables were analyzed: withdrawal from this study due to NIV or death, excursion, velocity, thickness, thickening fraction, and spirometric and respiratory muscle function values. Results: A total of 41 patients were included. A total of 24 (61.5%) patients left this study before the final year: 17 due to initiation of NIV, 4 due to clinical deterioration without NIV, and 3 due to death. Statistically significant moderate correlations were observed between diaphragmatic excursion and velocity and FVC and supine FVC (p < 0.001) and with MIP and the SNIP test (p < 0.05). No correlation was observed with thickening fraction. Additionally, lower baseline values in excursion were significantly associated with study withdrawal, along with reduced lung function (FVC, supine FVC, and MEP (p < 0.001). Conclusions: assessing diaphragmatic excursion by ultrasonography may serve as a useful tool for monitoring patients with ALS.